Differential outcomes of jaw bone position after surgical-orthodontic treatment in three types of skeletal Class III asymmetry patients - Yi-Jane Chen; Cheng-Yen Tsai; Zwei-Chieng Chang; Chung-Chen Yao; Sang-Heng Kok (Journal of the Formosan Medical Association)
Background/Purpose: Facial asymmetry is common in Class III patients requiring orthognathic surgery. This study aimed to analyze jaw bone position after surgical-orthodontic treatment in three types of skeletal Class III asymmetry patients. Methods: The retrospective study included 30 Class III patients who underwent surgical-orthodontic treatment comprising LeFort I osteotomy and bilateral sagittal split osteotomy (BSSO) without genioplasty. Cone-beam computed tomography (CBCT) images obtained before surgery (T1) and after post-surgical orthodontic treatment (T2) were superimposed with voxel-based registration. Patients were classified into three groups based on T1 CBCT scans. Groups 1 and 2 exhibited menton and ramus deviated to the same side. Menton deviation was larger than ramus width asymmetry in group 1, while the reverse was true for group 2. Group 3 had menton deviation contralateral to the side with greater ramus width. Results: Menton deviation after treatment was improved in all groups. Ramus width asymmetry and coronal ramus angle difference decreased in groups 1 and 2. Neither improvement nor deterioration of ramus width asymmetry was noted for group 3. Comparing to groups 1 and 2, group 3 had greater roll and yaw rotations of distal segment, more upward pitch of proximal segment on chin deviation side, and largest inward yaw as well as backward translation of proximal segment on non-deviation side. Conclusion: The positional changes of osteotomy segments differed among three types of mandibular asymmetry. Special attention should be given to the atypical mandibular asymmetry with mandibular body and ramus deviating to opposite directions during surgical correction of jaw deflection.